1988
DOI: 10.1055/s-0038-1642570
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis Associated with Antiphospholipid Antibodies Cannot Be Explained by Effects on Endothelial and Platelet Prostanoid Synthesis

Abstract: SummaryThe effect of 23 antiphospholipid antibody positive SLE sera, 4 antiphospholipid antibody negative SLE sera and 17 control sera on endothelial prostacyclin and platelet thromboxane A? production was studied. Endothelial cells and platelets were stimulated with different agonists. Depending on the stimulus used, 4-19% of the SLE sera inhibited the prostacyclin release, whereas 4-28% enhanced prostacyclin production. Our data suggest that the pathophysiological mechanisms underlying decreased prostacyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A good number of suggestions have come forth as to the mechanism of action of this molecule [12][13][14][15][16], however, none have actually been proven to be the mechanism of action or to define the pathogenesis of thrombi in the antiphospholipid syndrome [17]. Yet, the possibility that the antiphospholipid antibody binds directly to platelets, which results in platelet aggregation, has occasionally been alluded to [2], but has not been seriously investigated until very recently [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A good number of suggestions have come forth as to the mechanism of action of this molecule [12][13][14][15][16], however, none have actually been proven to be the mechanism of action or to define the pathogenesis of thrombi in the antiphospholipid syndrome [17]. Yet, the possibility that the antiphospholipid antibody binds directly to platelets, which results in platelet aggregation, has occasionally been alluded to [2], but has not been seriously investigated until very recently [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Second, and probably closely related, how does it simultaneously inhibit plasma coag ulation in the test tube? A good number of suggestions have come forth as to the mechanism of action of this molecule [12][13][14][15][16], however, none have actually been proven to be the mechanism of action or to define the pathogenesis of thrombi in the anti phospholipid syndrome [17], Yet, the possibility that the antiphospholipid antibody binds directly to platelets, which results in platelet aggregation, has occasionally been allud ed to [2], but has not been seriously investigated until very recently [18,19], This mechanism occurred to us in observ ing the platelet neutralization procedure of Howard and Firkin [20] for detecting LAC [21], In this test, the addition of platelets to the plasma-coagulating system neutralizes the inhibition of coagulation by LAC. The neutralization of the LAC apparently is due to its preferential binding to the phospholipids in the platelet membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that ACA-positive sera might increase thromboxane formation in platelets. 23 It is known that treatment with aspirin-a drug that effectively blocks thromboxane A 2 production in platelets-is effective in the prevention of repeated abortion, 24 a clinical condition in which the presence of APAs has been found to be consistently increased. 25 All the patients with ACAs who were involved in our study had a previous history of thrombosis.…”
mentioning
confidence: 99%